PENGGUNAAN KAMERA VIDEO SEBAGAI ALTERNATIF ALAT UKUR GETARAN LATERAL PADA PERMESINAN DI KAPAL - Poernomo, Heroe (Department of Naval Architecture - Diponegoro University, 2012)
General method which often used in measuring lateral vibration in the ship is vibration-meter. This method has some limitation like complicated, high cost, just can measure vibration at house of bearing and cannot measure vibration at shaft which rotated. Other limitation is the optimum censor at high rotation up to 600 rpm. Based on the above condition, this research conduct the vibration measurement with the alternative method, that is Digital Image Processing. This Method is simple and expense required cheaper if compared to previous method. Vibration which can be measured not limited at house of bearing but it can at all of shaft and can be used at object with the lower rotation. This method just use camera to record vibration object and thenÂ analyse all frames of picture to know displacement value by matlab software. Experiments to get vibration data at berputar shaft with use 2 method, there are digitalÂ image processing and vibration-meterÂ as validation. The shaft with diameter 5 mm and 10 mm rotate at drilling machine with 280 rpm and 550 rpm. The vibration data take by two methods together in the spanning same time. Based on result of analysis vibration data from second methods can be pulled a conclusion that vibration measurement with the Digital Image Processing after validation and compared to vibration-meter have tend the same value, so the Digital Image Processing method can be used as alternative method in measurement of vibration at berputar shaft rotate